2018
DOI: 10.1371/journal.pbio.2004893
|View full text |Cite
|
Sign up to set email alerts
|

Dietary rescue of lipotoxicity-induced mitochondrial damage in Peroxin19 mutants

Abstract: Mutations in peroxin (PEX) genes lead to loss of peroxisomes, resulting in the formation of peroxisomal biogenesis disorders (PBDs) and early lethality. Studying PBDs and their animal models has greatly contributed to our current knowledge about peroxisomal functions. Very-long-chain fatty acid (VLCFA) accumulation has long been suggested as a major disease-mediating factor, although the exact pathological consequences are unclear. Here, we show that a Drosophila Pex19 mutant is lethal due to a deficit in medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The core genes, i.e., common in all the GO categories of cluster 1, in HFD-treated female heads including Mtpalpha (Mitochondrial trifunctional protein (MTP) α subunit), yip2 (yippee interacting protein 2) and CG12262 (Medium-chain acyl-CoA dehydrogenase), all are upregulated ( Fig 5B ) only in the female heads and are involved in mitochondrial β-oxidation. For example, Mtpalpha catalyzes long-chain fatty acid β-oxidation [ 39 ], yip2 is a target gene of hepatocyte nuclear factor 4 ( Hnf4 ) involved in lipolysis [ 40 ] and the role of CG12262 in medium-chain-acyl-CoA dehydrogenase activity is inferred from its sequence similarity with ACADM (Acyl-CoA Dehydrogenase Medium Chain). As such, the baseline expression itself in female flies are high; it is further increased by the HFD treatment in the heads, which is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…The core genes, i.e., common in all the GO categories of cluster 1, in HFD-treated female heads including Mtpalpha (Mitochondrial trifunctional protein (MTP) α subunit), yip2 (yippee interacting protein 2) and CG12262 (Medium-chain acyl-CoA dehydrogenase), all are upregulated ( Fig 5B ) only in the female heads and are involved in mitochondrial β-oxidation. For example, Mtpalpha catalyzes long-chain fatty acid β-oxidation [ 39 ], yip2 is a target gene of hepatocyte nuclear factor 4 ( Hnf4 ) involved in lipolysis [ 40 ] and the role of CG12262 in medium-chain-acyl-CoA dehydrogenase activity is inferred from its sequence similarity with ACADM (Acyl-CoA Dehydrogenase Medium Chain). As such, the baseline expression itself in female flies are high; it is further increased by the HFD treatment in the heads, which is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…Margret Bülow talked about their recent work on protein catabolism in a Peroxin (Pex) 19 mutant. Pex19 mutants show dysregulated ceramide synthase activity, which leads to lipid catabolism, accumulation of free fatty acids and mitochondrial hyperactivity (Sellin et al 2018 ). Analysis of the Pex19 mutant lipidome revealed that due to the accumulation of very long-chain fatty acids that is characteristic for peroxisome dysfunction, ceramide-derived sphingolipids incorporate longer fatty acids.…”
Section: Session 1: Chair: Noa Dahan Weizmann Institute Of Science Israelmentioning
confidence: 99%
“… Bulow et al (2018) showed that homozygous Pex19 mutation results in an increase in free fatty acids, leading to lipotoxicity via altered abundance in MCFAs due to down-regulated mitochondrial lipolysis. Restoring MCFA abundance by dietary supplementation rescued the phenotype in flies and PEX19 patient cells ( Sellin et al, 2018 ). Similar changes in MCFA abundance and altered mitochondrial lipolysis were observed in Pex2 , Pex3 and Drp1 mutant larvae ( Chao et al, 2016 ; Bulow et al, 2018 ; Sellin et al, 2018 ).…”
Section: Conservation Of Peroxisome Metabolic Activity In Dmentioning
confidence: 99%
“…Restoring MCFA abundance by dietary supplementation rescued the phenotype in flies and PEX19 patient cells ( Sellin et al, 2018 ). Similar changes in MCFA abundance and altered mitochondrial lipolysis were observed in Pex2 , Pex3 and Drp1 mutant larvae ( Chao et al, 2016 ; Bulow et al, 2018 ; Sellin et al, 2018 ). In the case of Drp1 mutants, aberrant mitochondrial morphology was observed in nervous and muscle tissue ( Chao et al, 2016 ).…”
Section: Conservation Of Peroxisome Metabolic Activity In Dmentioning
confidence: 99%
See 1 more Smart Citation